Calcul algébrique

Développement et factorisation


  1. Développer les expressions:
    $A(x)=\lp1+3x\rp^2-\lp1-3x\rp^2  et   $B(x)=\left( 2x+3\rp\left( x+1\rp+\left(2x-1\rp^2

  2. Factoriser les expressions:
    $C(x)=(2x-2)(2x-6)-(x-3)(2x-6)  et   $D(x)=(-x+3)(2x-1)+(-x+3)

Solution:


  1. $A(x)=\lp1+3x\rp^2-\lp1-3x\rp^2=1+6x+9x^2-\lp1-6x+9x^2\rp=12x
    $B(x)=\left( 2x+3\rp\left( x+1\rp+\left(2x-1\rp^2=2x^2+2x+3x+3+4x^2-4x+1=6x^2+x+4

  2. $C(x)=(2x-2)(2x-6)-(x-3)(2x-6)=(2x-6)\Bigl[ (2x-2)-(x-3)\Bigr]=(2x-6)(x+1)
    $D(x)=(-x+3)(2x-1)+(-x+3)=(-x+3)\Bigl[ (2x-1)+1 \Bigr]=(-x+3)(2x)


Autres ressources